2017
DOI: 10.5430/jnep.v8n3p144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of application of peer learning strategy on obstetric and gynecological nursing students' clinical performance

Abstract: Background and objective: Peer learning is an efficient educational technique for nursing students. It equips them up for their future roles as instructors, promotes their psychomotor skills, and establishes their self-esteem. The current study aims to determine the effect of application of peer learning strategy on obstetric and gynecological nursing students' clinical performance. Methods: Quasi-experimental design was utilized. The study was carried out in the obstetric and gynecology skills lab at the Facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
2
3
0
2
Order By: Relevance
“…When PIVC knowledge and skills of students were evaluated, there was no statistical difference between the knowledge and skill mean scores of the students who had peer mentoring model and who had traditional teaching model. Review of the studies in the literature, which evaluated knowledge and skill effects of peer mentorship revealed that knowledge and skills of students increased with the help of collaborative learning [7,9,21]. The study conducted by El-Sayed et al [8], found that peer mentoring was more effective than the classical teaching method in increasing the knowledge and skills of the students [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When PIVC knowledge and skills of students were evaluated, there was no statistical difference between the knowledge and skill mean scores of the students who had peer mentoring model and who had traditional teaching model. Review of the studies in the literature, which evaluated knowledge and skill effects of peer mentorship revealed that knowledge and skills of students increased with the help of collaborative learning [7,9,21]. The study conducted by El-Sayed et al [8], found that peer mentoring was more effective than the classical teaching method in increasing the knowledge and skills of the students [8].…”
Section: Discussionmentioning
confidence: 99%
“…The most important roles of mentors are to help, support, guide, and encourage student nurses to learn new skills, to adapt to new behaviors, to gain new attitudes, to combine theory with practice [9,11,14,15]. Studies report that peer mentoring in laboratory or clinical settings positively affects cognitive, psychomotor, and affective development of the mentee student [8,9], reduces students' fear, stress, and anxiety during the practice of these skills [3,16,17], and provides self-confidence, critical thinking, communication skills and gives opportunities to develop leadership skills [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that evaluated the effectiveness of peer education; most of the participants feel more confident and knowledgeable, and their learning capacities and test performance increase (Essa, Al-Battawi, Ali Abd El Salam El Demerdash, & Elsoud Ahmed, 2018;Pålsson, Mårtensson, Swenne, Ädel, & Engström, 2017). The active participation of the students in the learning process through peer education enables them to better understand, internalize and remember what they have learned more clearly (Ünver & Akbayrak, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde de akran eğitiminin hemşirelik eğitiminde öğrencinin katılımını ve öğrenme deneyiminin kalitesini arttırmak için başarıyla kullanıldığı ve öğrenciye birçok yarar sağladığı belirtilmektedir. Essa et al (2018), Pålsson ve diğ. (2017), akran eğitiminin öğrencilerin klinik ortamda kaygılarını azalttığını, özgüvenlerini arttırdığını, mesleki gelişimlerine katkıda bulunduğunu ve profesyonel hemşirelik rollerini yerine getirmelerini kolaylaştırdığını saptamıştır.…”
Section: Hemşirelik Eğitiminde Akran Eğitiminin Kullanımıunclassified
“…Ancak günümüzde bilgi ve teknolojide, sosyo-kültürel, siyasi alanlarda yaşanan değişme ve gelişmeler, hemşirelik eğitiminin öğrencinin aktif katılımını, yaratıcı düşünmesini, sorumluluk üstlenmesini sağlayacak öğrenci merkezli aktif öğretim yöntemlerine temellenmesini zorunlu kılmaktadır (Banning, 2005;Parkin, 2006;Bensfield, Solari-Twadell And Sommer, 2008). Bu yöntemlerden biri de, akranların işbirliği içinde çalışacakları, birbirlerinden öğrendikleri, birbirlerinin öğrenmelerine yardım ettikleri ve öğreterek öğrendikleri, öğrenme sorumluluğunu kendilerinin üstlendikleri Akran Eğitimi'dir (Essa et al, 2018;Nestel and Kidd, 2003;Pålsson ve diğ., 2017;Parkin, 2006;Ünver ve Akbayrak, 2013).…”
Section: Introductionunclassified